Analysis of the Effect of Credit Restructuring on the Liquidity Level of Banks Listed on the Indonesian Stock Exchange (IDX) Before and After the COVID-19 Pandemic - Rahmatulloh, Muhammad Wilszam; Bambang (International Journal of Business and Applied Economics, 2024)
This research aims to determine the effect of credit restructuring on liquidity levels through the Loan to Deposit Ratio before the COVID-19 pandemic and after the COVID-19 pandemic. The data used is secondary data in financial reports for 2019 before the COVID-19 pandemic and 2020-2023 after the COVID-19 pandemic. The results of this research show that the Loan to Deposit Ratio experienced a decrease, as evidenced by the results of descriptive statistical research, which showed the average difference (Loan to Deposit Ratio decreased by 0.1423.